Calculations of Flow Boiling Heat Transfer in a Minichannel Based on Liquid Crystal and Infrared Thermography Data. Issue 3 (11th February 2017) - Piasecka, Magdalena; Strąk, Kinga; Maciejewska, Beata
ABSTRACT: This paper analyzes results concerning flow boiling heat transfer in two parallel, asymmetrically heated vertical minichannels. The heating element for FC-72 Fluorinert flowing in the minichannels was a thin foil with an enhanced surface on the side in contact with the fluid. In one minichannel, changes in the temperature on the smooth side of the foil were monitored using liquid crystal thermography. Changes in the temperature on the outer surface of the glass in one minichannel and on the foil in the other minichannel were observed using infrared thermography. The heat transfer coefficient at the foil–fluid interface was calculated on the basis of one- and two-dimensional heat transfer models. In the two-dimensional method, the distribution of temperature on the enhanced side of the foil was determined by solving the inverse heat conduction problem. The governing equations were solved using the finite-element method combined with the Trefftz functions used as shape functions. The temperature measurement points were located at the boundary nodes of elements. Local values of the heat transfer coefficient calculated with the one- and two-dimensional models were analyzed in the function of the distance from the minichannel inlet. The values obtained with the two models were similar.